Determining the ratio of the number of recoil electrons to the number of photoelectrons using a new method (Nexo Revista Científica, 2021)
The problem in question is relevant due to discrepancy between the results of theoretical and known experimental studies of various interactions of ionizing emission photons with substances, in particular, photo effect and Compton scattering of these photons. The study aimed at carrying out specific measurements using a new method of simultaneously determining the ratio of the number of recoil electrons to the number of photoelectrons. Analysis of the results showed that there are significant discrepancies between theoretical calculations and experimental data. New values of simultaneously measured ratios of cross-sections for heavy atoms using a method invented by the author, and old measurements of these ratios for light atoms usingWilson cloud chamber, when compared with theoretical calculations, show that a significant (by one order and more) one-direction discrepancy is seen for X-ray and gamma emissions over a range of energies in question.It is shown that these discrepancies might be attributed to the fact that an atomic electron is in a free state for a while. Compton scattering occurs with a free electron; photo effect involves only bound electrons. Therefore, Compton scattering cross section is proportional to a period of time, during which electron was in a free state, whereas photo effect cross section is proportional to a time period, during which electron was in a bound state. The article materials might be helpful to perform both fundamental, and applied studies on interaction of light quanta with substance including modelling the phenomena under examination.